1997
DOI: 10.1088/0960-1317/7/1/002
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced field emission from microtips covered by ultrathin layers

Abstract: The influence of different types of covering on electron field emission from silicon tips has been studied. For this a series of silicon tip array structures, namely (i) structures with porous silicon layers on the tops of the tips, (ii) tips covered with carbon films, (iii) silicon tips implanted by hydrogen, and (iv) cesium-enriched silicon tips, has been prepared and investigated. The comparison and characterization of various structures using effective work functions, field enhancement factors, and effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…[11][12][13] The relation between effective E gap and X is also fulfilled to within 0.5 eV: E gap ϩXϭ5 eV was obtained by Robertson, 11 E gap ϩX T ϭ4.5Ϫ5.5 eV also was obtained in our works. 12,13 So, for these cases it is possible to estimate the indicated quantities from relation ͑1͒ and, in addition, some technology parameters like hydrogen content, refraction index n, etc., can be estimated. [22][23][24] Calculations of the effective lattice constants from the data of valence radii of atoms r as Lϭrϫ4/ͱ3 have been performed for the following compositions: CH 4 , SiH 4 , and GeH 4 .…”
supporting
confidence: 69%
See 2 more Smart Citations
“…[11][12][13] The relation between effective E gap and X is also fulfilled to within 0.5 eV: E gap ϩXϭ5 eV was obtained by Robertson, 11 E gap ϩX T ϭ4.5Ϫ5.5 eV also was obtained in our works. 12,13 So, for these cases it is possible to estimate the indicated quantities from relation ͑1͒ and, in addition, some technology parameters like hydrogen content, refraction index n, etc., can be estimated. [22][23][24] Calculations of the effective lattice constants from the data of valence radii of atoms r as Lϭrϫ4/ͱ3 have been performed for the following compositions: CH 4 , SiH 4 , and GeH 4 .…”
supporting
confidence: 69%
“…[8][9][10][11][12][13][14][15] Hence, the energy gap will decrease in accordance with a simple relation…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation also has been observed between increasing film roughness (at low depositionẽ nergy) and a lower & for FE [15]. In addition, several groups have demonstrated that J ultrathin a-D coatings (ranging from -2 nm to -30 nm) can enhance FE fi-om Spindt tip c F arrays [16][17][18][19]. This may be a hot-electron effect with the electrons injected from a -c metallic substrate layer and tunneling through the a-D coating [18].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The low electron affinity, chemical endurance, and high thermal conductivity of DLC films allow one to greatly enhance the emission parameters of Si emitters. To improve the emission properties of silicon tip emitters coating with diamond-like carbon ͑DLC͒ films is widely used.…”
Section: Introductionmentioning
confidence: 99%